OPTION PRICING FOR A JUMP DIFFUSION MODEL WITH FRACTIONAL - Intarasit, A.; Sattayatham, P. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2011)
An alternative stochastic volatility model with jumps is proposed, in which stock prices follow a jump diffusion model and their stochastic volatility follows a fractional stochastic volatility model. By using an approximate method, we find a formulation for the European-style option in terms of the characteristic function of tail probabilities.